Modelling the future impacts of climate change on sediment yield for a semi-arid catchment in South Africa using SHETRAN - Barnardt, Georg Frederik (Stellenbosch : Stellenbosch University, 2021)
Thesis (MEng)--Stellenbosch University, 2021.